2007
DOI: 10.1091/mbc.e05-11-1027
|View full text |Cite
|
Sign up to set email alerts
|

Parkin-mediated Monoubiquitination of the PDZ Protein PICK1 Regulates the Activity of Acid-sensing Ion Channels

Abstract: Mutations in the parkin gene result in an autosomal recessive juvenile-onset form of Parkinson's disease. As an E3 ubiquitin-ligase, parkin promotes the attachment of ubiquitin onto specific substrate proteins. Defects in the ubiquitination of parkin substrates are therefore believed to lead to neurodegeneration in Parkinson's disease. Here, we identify the PSD-95/Discs-large/Zona Occludens-1 (PDZ) protein PICK1 as a novel parkin substrate. We find that parkin binds PICK1 via a PDZ-mediated interaction, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
99
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 70 publications
(134 reference statements)
5
99
1
Order By: Relevance
“…Among the 24 proteins identified by mass spectrometry (Table 1), 16 were associated with the postsynaptic density (Husi et al, 2000;Collins et al, 2004;Husi, 2004). It has previously been shown that proteins in the postsynaptic density are regulated by the ubiquitin-proteasome system and that these changes are activity related and reversible (Colledge et al, 2003;Ehlers, 2003;Bingol and Schuman, 2004;Joch et al, 2007). We show a structural component, evident during rapid tolerance, dendritic spine loss, which has been reported previously with sublethal doses of ischemia (Park et al, 1996;Hasbani et al, 2001a).…”
Section: Discussionsupporting
confidence: 79%
“…Among the 24 proteins identified by mass spectrometry (Table 1), 16 were associated with the postsynaptic density (Husi et al, 2000;Collins et al, 2004;Husi, 2004). It has previously been shown that proteins in the postsynaptic density are regulated by the ubiquitin-proteasome system and that these changes are activity related and reversible (Colledge et al, 2003;Ehlers, 2003;Bingol and Schuman, 2004;Joch et al, 2007). We show a structural component, evident during rapid tolerance, dendritic spine loss, which has been reported previously with sublethal doses of ischemia (Park et al, 1996;Hasbani et al, 2001a).…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, the ubiquitinated isoforms do not show a typical ubiquitination "ladder" but instead appear to reflect a pattern of one and three or four ubiquitin adducts. Although it remains to be shown that Parkin directly mediates this ubiquitination, there is evidence that Parkin can mediate monoubiquitination (33)(34)(35)(36)(37) and K27 (23) and K63 linkages (38,39). These modes of ubiquitination are not typically linked to proteasome degradation, and there is growing speculation that important pathogenic functions of Parkin may be proteasome independent (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently unclear how Drp1 is recruited to mitochondria from the cytoplasm to promote the fission event (25), although Drp1 is subjected to multiple posttranslational modifications, including phosphorylation (45,46), SUMOylation (47)(48)(49), and ubiquitination (50,51), raising the possibility that one or more of these posttranslational modifications regulates the recruitment of Drp1 to mitochondria. Because Parkin can apparently promote both degradative and nondegradative forms of ubiquitination (52,53), the ubiquitination of Drp1 by Parkin could act in a nondegradative fashion to promote Drp1 to assemble with mitochondria to activate fission. Alternatively, the PINK1/Parkin pathway may indirectly promote mitochondrial fission by inhibiting a key component of the mitochondrial fusion machinery.…”
Section: Discussionmentioning
confidence: 99%